APLIKASI PEMBELAJARAN INTEGRAL BERBASIS WEB - Juwairiah Juwairiah Juwairiah; Retno Wulan Sari; Wilis Kaswidjanti (Telematika, 2010)
Mathematics lessons, is one lesson that is not liked by the students. Hearing the words of mathematics, will only think of the word difficult by the students. This is because the medium of learning that there are still less attractive. The material is a material that is considered integral to the most difficult of lessons. Thus the need for an application that can be used to study the material with the pattern of applied learning and interesting .. System development method used is waterfall method of analysis, design, programming, testing, and maintenance. This application uses the programming language PHP, MySql as database, Dreamweaver, Macromedia Flash for animation and Photoshop as graphic design. Web server used is Apache.